2008
DOI: 10.1098/rspb.2008.0733
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete reproductive isolation following host shift in brood parasitic indigobirds

Abstract: Behavioural and molecular studies suggest that brood parasitic indigobirds (Vidua spp.) rapidly diversified through a process of speciation by host shift. However, behavioural imprinting on host song, the key mechanism promoting speciation in this system, may also lead to hybridization and gene flow among established indigobird species when and if female indigobirds parasitize hosts already associated with other indigobird species. It is therefore not clear to what extent the low level of genetic differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…However, it is not always obvious that habitat or resource imprinting should directly affect mating preferences. In the Vidua indigobirds, there is an imprinting effect of host song, such that nest parasites raised by the same host species tend to mate assortatively owing to learned elements of their own songs and preferences [103,104]. In many phytophagous insects, mating occurs on or near the host plant [102,105], making plant choice a "magic trait" simultaneously effecting ecological and sexual differentiation [31].…”
Section: Phenotypic Plasticity and The Evolution Of Reproductive Isolmentioning
confidence: 99%
“…However, it is not always obvious that habitat or resource imprinting should directly affect mating preferences. In the Vidua indigobirds, there is an imprinting effect of host song, such that nest parasites raised by the same host species tend to mate assortatively owing to learned elements of their own songs and preferences [103,104]. In many phytophagous insects, mating occurs on or near the host plant [102,105], making plant choice a "magic trait" simultaneously effecting ecological and sexual differentiation [31].…”
Section: Phenotypic Plasticity and The Evolution Of Reproductive Isolmentioning
confidence: 99%
“…; Balakrishnan et al. ), we know of no case where learning has been shown to be a major factor leading to speciation.…”
mentioning
confidence: 94%
“…Intriguingly, with a single exception involving the unusual brood parasitic indigo birds (Vidua spp. ), which imprint on their host (Payne et al 2000;Sorenson et al 2003;Balakrishnan et al 2009), we know of no case where learning has been shown to be a major factor leading to speciation.…”
mentioning
confidence: 99%
“…7B) supports the hypothesis that gene flow 812 among Vidua species has increased the level of gene tree discor-813 dance in this genus, and that differences between the genera are 814 not due solely to different timescales for speciation. 815 Hybridization between Vidua species has been documented 816 , and is likely facilitated by mate choice 817 behaviors that are shaped by host imprinting (Payne et al, 2000), 818 sympatry between ancestral and incipient species, and imperfect 819 host fidelity by female parasites (Balakrishnan et al, 2009). An 820 additional factor that may contribute to discordance among loci 821 is the possibility that a given parasitic species derives from multi- (Fig.…”
mentioning
confidence: 99%